Deficiency of complement component C3 is associated with accelerated removal of soluble 123I-labelled aggregates of IgG from the circulation. - Halma, C (1992)
Complement and erythrocyte complement receptors CR1 (CD35) play an important role in the clearance of immune complexes. We studied the elimination of soluble 123I-labelled aggregates of human immunoglobulin G (123I-AIgG), used as a model for immune complexes, in two patients with a congenital and two patients with an acquired deficiency of complement component C3, and compared these with 10 healthy controls. The first disappearance halflife of 123I-AIgG was shorter (3.3 +/- 0.4 versus 7.0 +/- 0.4 min in the controls, P = 0.005) and maximal hepatic uptake of aggregates was increased in the C3 deficient patients (maximal liver/background ratio 3.6 +/- 0.4 versus 2.7 +/- 0.2 in controls, P = 0.04). Apparently, in the absence of C3, removal of circulating immune complexes by the liver is accelerated, probably through Fc receptor-dependent mechanisms.